Controlled atmosphere storage for preservation of Salicornia ramosissima - Raposo, M. F. (2010)
Salicornia is a halophytic plant that grows near salt marshes and salted wetlands, very rich in vitamins, minerals and highly unsaturated oils. Because of its biochemical composition and despite salinity, Salicornia is considered a gourmet product. Since stems present a short shelf life, the aim of this work was to evaluate the effect of controlled atmosphere on quality of Salicornia ramosissima during four weeks at 4°C. Vitamin C and chlorophyll contents were determined, and microbiological and sensory analyses were performed. Salicornia shoots preserved better the visual appearance and L-ascorbic acid for three weeks of storage under CA with 3% oxygen and 10% carbon dioxide, although chlorophyll was better preserved in air. All samples were microbiologically safe during all storage. CA storage, especially in 3% oxygen and 10% carbon dioxide seems to be a good method to preserve Salicornia ramosissima shoots